The Impact and Strategies of EFL Students Using Social Media Platforms in Overcoming Online Learning Challenges - Fitrisia, Dohra; Aufa, Nawal; Yusuf, Yunisrina Qismullah; Delavari, Hilda (Institut Agama Islam Negeri Kudus, 2025)
This study explores how EFL students at two public universities in Banda Aceh, Indonesia, utilize social media platforms to support their English language learning. Employing a mixed-method approach, the research integrates both qualitative and quantitative methods. Data were collected through a questionnaire completed by 100 students and interviews conducted with 10 participants. Fundamental statistical analysis was used to evaluate questionnaire responses, while interview data were analyzed through data reduction, display, and conclusion verification. The findings reveal that students frequently use social media to study, complete assignments, and access current information. They perceive improved vocabulary, pronunciation, and listening skills through online learning. However, the study also identifies technical issues, shared gadget usage, and time management. To address these obstacles, students adopted strategies such as informing lecturers about technical problems, maintaining communication with classmates, ensuring adequate Internet quota, and developing effective time management and discipline. This research highlights the benefits and challenges of integrating social media into EFL learning and yields important findings on strategies students employ to navigate these difficulties. The study contributes to a deeper understanding of the role of social media in language education and offers practical implications for educators seeking to enhance EFL learning through digital platforms.